The impact of the COVID-19 pandemic on pleural infection incidence: a UK multicentre retrospective analysis. Issue 3 (1st August 2022) - Bedawi, Eihab O.; Ur Rehman, Khalil; Sivakumar, Deepan P.; Ferguson, Katie; Ajmal, Syed; Graham, Emma; Panchal, Rakesh K.; Corcoran, John P.; Blyth, Kevin G.; Rahman, Najib M.; West, Alex
The fall in non-coronavirus disease 2019 (non-COVID-19) respiratory viruses, including seasonal influenza, during the pandemic is well reported [1–4]. It is thought to be a result of a combination of social distancing, lockdowns, improved hand hygiene and potentially virus–virus interactions and cross-protection affecting population dynamics. However, as vaccines weaken the transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), clinicians remain vigilant for a potential resurgence of other respiratory pathogens and the implications of an ongoing rise in new SARS-CoV-2 variants. There was a significant reduction in pleural infection incidence, by almost a third, in the year following the start of the #COVID19 pandemic. Public health measures enforced during this period are likely to have played a significant role. https://bit.ly/3QAPPR9